2011
DOI: 10.1007/s10531-011-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Are grasslands important habitats for soil microarthropod conservation?

Abstract: Biodiversity has been a focal aim of environmental protection since the Rio conference, but only with the beginning of the new millennium did soil biodiversity become an important aspect of international policy. Edaphic fauna play a key role in many soil functions, such as organic matter decomposition, humus formation and nutrient element cycling; moreover, affect the porosity, aeration, infiltration and distribution of organic matter in soil horizons, modifying soil structure and improving its fertility. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 34 publications
9
63
1
Order By: Relevance
“…13 Average EMI value of the taxonomic group with major contribution to dissimilarity between Tolfa, Vetralla, Canale Monterano and Tarquinia Turkey oak plots (SIMPER procedure; cut off, ≈70 %). The analyses were performed after removing the heavily impacted plots (tractor/car transit, trampling and sea effect) 70 to 200; Gardi et al 2002;Menta et al 2008Menta et al , 2011, in managed chestnut woodland (157-107; Paparatti and Peroni, personal communication), in vaccinietum (Empetro-Vaccinietum gaultherioidis) and alpine fields (Anthoxantho-Brachypodietum genuensis), (QBS-ar average values are equal to 135 and 190, respectively;Leoni 2008) and in degraded areas, such as covered dumps (QBS-ar value was lower than 80; Menta et al 2008). A previous study (Callaham et al 2006) indicated a clear gradient of decreasing diversity of macroinvertebrate soil communities from hardwood stands to pine stands followed by pastures and cultivated fields.…”
Section: Discussionmentioning
confidence: 99%
“…13 Average EMI value of the taxonomic group with major contribution to dissimilarity between Tolfa, Vetralla, Canale Monterano and Tarquinia Turkey oak plots (SIMPER procedure; cut off, ≈70 %). The analyses were performed after removing the heavily impacted plots (tractor/car transit, trampling and sea effect) 70 to 200; Gardi et al 2002;Menta et al 2008Menta et al , 2011, in managed chestnut woodland (157-107; Paparatti and Peroni, personal communication), in vaccinietum (Empetro-Vaccinietum gaultherioidis) and alpine fields (Anthoxantho-Brachypodietum genuensis), (QBS-ar average values are equal to 135 and 190, respectively;Leoni 2008) and in degraded areas, such as covered dumps (QBS-ar value was lower than 80; Menta et al 2008). A previous study (Callaham et al 2006) indicated a clear gradient of decreasing diversity of macroinvertebrate soil communities from hardwood stands to pine stands followed by pastures and cultivated fields.…”
Section: Discussionmentioning
confidence: 99%
“…In a general study on microarthropods, Menta et al (2011) showed taxonomic assemblages to be clearly different between grasslands and agricultural lands, a pattern that was largely driven by differences in the mites and springtails. A similar distinction was observed for soil mites by Dirilgen et al (2015) across a north-south European transect.…”
Section: Succession In Soil Mite Communities Following a Transition Fmentioning
confidence: 99%
“…A similar distinction was observed for soil mites by Dirilgen et al (2015) across a north-south European transect. Moreover, microarthropods are less abundant in intensively managed arable soils than in soils of extensively managed systems, such as grasslands (Giller et al, 1997;PostmaBlaauw et al, 2010;Menta et al, 2011). Thus, the transition from an agricultural system to an extensively managed grassland can be expected to result in clear changes in the mite community of the soil.…”
Section: Succession In Soil Mite Communities Following a Transition Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The EMI is a valué assigned at each taxonomic group and ranges from 1 to 20, from the lowest to the greatest adaptation to the soil. For more details see Gardi et al (2008); Tabaglio et al (2009);Menta et al (2011);Blasi et al (2013) and Menta et al (2014).…”
Section: Soil Biodiversity íNdicesmentioning
confidence: 99%